The Communicational Dimension for the Inclusion of People with Disabilities in Organization - Pereira, Ana; de Abreu Figueiró, Gabriel (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2020)
This article aims to identify the communication processes existing between organizations and their workers with disabilities, discussing the importance of building accessible relationships and the role of communication in the inclusion of these subjects in the work environment. Given the importance of the subject of the social and professional development of people with disabilities and for the construction of a more inclusive society, a research is proposed that points out the contributions that a communication professional, especially in public relations, can bring as a result of the exercise of their activity in the process of inclusion of these subjects within the organizations. For the accomplishment of this work, a case study was developed with two organizations that already have inclusion programs established. From the results obtained, one can perceive the existence of spaces of social exclusion even in inclusive processes and the importance of the use of assistive solutions as tools that help the construction of accessible communication within the organizations, in order to provide greater professional development and of the subjects with disabilities.